EFFICIENCY OF SOYBEAN PRODUCTION AS AN ALTERNATIVE SOURCE OF BIOFUEL IN THE ENERGY MARKET - Shamuratova Nazgul Balabaevna; Karimova L. Zh.; Dosmukhambetova R.; Kudaibergenova L. Zh.; Mazhitova L.G. (Scientific Journal of Pedagogy and Economics, 2021)
Active management in the oil and gas industry needs to take in account knowledge not only about fossil fuels but also various types of alternative fuels like biofuels. This thesis goal is to analyze the economics of producing Bio-Crude oil from a plant called Jatrophae curcadis, (or also known as “purging nut”). It is nowadays growing around subtropical regions of the North American continent, especially in Mexico, and southern Asia, and with lower yield can grow even in arid wastelands of Central Asia (in arid Mali it is grown to hold wildlife from plants). It is the very undemanding plant so the biofuel produced from it can be very cheap compared to other biofuels. Biofuels are viewed as a possible fuel of the future. Concerning energy for cars there is intense “competition” stemming from electricity and rising in popularity due to modern research is also hydrogen. In general, biofuels are nowadays strongly supported in the European Union as well as in the United States of America and many other regions of the world. The oil produced from this plant is not being traded on commodities markets yet but is viewed as biofuel of the future as currently sold soybean oil and palm oil are according to my analysis more expensive in many areas of the world. Production of the plant seeds (nuts) when pressed leads to bio-crude oil which can be processed to biocrude. Economic analysis showed that given irrigation and good genetic selection of the plants to give higher production of seeds (price of the kg would be determining factor), the biocrude produced from the seeds has the potential to successfully compete with alternative fuels made from soybean or palm oils.